Comparison of the biodegradable polymer everolimus-eluting stent with contemporary drug-eluting stents: A systematic review and meta-analysis - Picard F; Pighi M; de Hemptinne Q; Airaksinen J; Vinco G; de Pommereau A; Biancari F; Varenne O (My University, 2022)
Despite similar efficacy and safety profile in pilot studies, bioresorbable polymer drug-eluting stents (BP-DES) could have potential benefit over latest generation durable polymer (DP)-DES by facilitating vessel healing, therefore reducing inflammation and neoatherosclerosis leading to enhanced clinical safety. Therefore, we sought to perform a meta-analysis of randomized clinical trials (RCTs) comparing the safety and efficacy of everolimus-eluting BP-DES (BP-EES) to second-generation DP-DES.\nWe conducted a systematic review and meta-analysis to examine the safety and efficacy of BP-EES in patients treated for coronary artery disease. We searched PubMed, Scopus, and the Cochrane Library through February 2018 for RCTs that included outcome data on BP-EES. We identified four eligible studies, which included a total of 4631 patients. Three studies reported a follow-up of one year and one study of five years. The BP-EES group, included 2315 patients and the DP-DES group included 2316 patients (1143 treated with DP-EES and 1173 treated with zotarolimus eluting DP-DES). Patient's characteristics were comparable between the two groups except for higher prevalence of prior MI in the DP-DES group (25.7 vs 22.5%, respectively, p = 0.001). Procedural characteristics were comparable among groups except for slightly longer lesions in the BP-EES group compared to the DP-DES group (mean 15.1 vs 14.9 mm, p = 0.04). No significant differences were observed for cardiac mortality (p = 0.72), occurrence of MI (p = 0.64), any TLR (p = 0.93), ST (p = 0.85) or major adverse cardiac events (p = 0.43).\nOverall, based on the available data BP-EES had similar one-year outcomes to contemporary DP-DES. Whether these devices could enhance clinical safety remains to be evaluated at longer follow-up.